IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMPN 6 PAYAKUMBUH TAHUN 2023 / 2024 - Indah Yonera Huriyanti; Rini Silvina; Ika Anggraeni (STKIP Pesisir Selatan, 2025)
Learning science using the lecture method without providing feedback and variations in learning can lead to low student learning outcomes and lack of student interest and motivation in learning. Various learning models and methods can be used in the learning process to improve learning outcomes and student interest. One of the learning models recommended in the Merdeka Curriculum is Project Based Learning. The purpose of this study was to determine the application of the Project Based Learning learning model to the learning outcomes of seventh grade students at SMP Negeri 6 Payakumbuh. This type of research is a quasi-experiment, with a population of all seventh grade students. The withdrawal of samples in this study was carried out by purposive sampling technique. The instrument used in this study was 25 objective questions that were valid and reliable. Data analysis technique used is t-test with real level (ɑ) = 0.05. The results of data analysis t table value = 2.63 and the value of t count = 1.68. It means that t count> t table, so the hypothesis is accepted at the 95% confidence level. It can be concluded that the Project Based Learning model can improve the learning outcomes of students in class VII.